Simultaneous Cardiac and Lung Surgery for Incidental Solitary Pulmonary Nodule: Learning from the Past - Zhang, R.; Wiegmann, B.; Fischer, S.; Dickgreber, N. J.; Hagl, C.; Krüger, M.; Haverich, A.; Zardo, P. (The Thoracic and Cardiovascular Surgeon, 2012)
Background Incidental solitary pulmonary nodules (ISPN) detected prior to scheduled cardiac surgery are rare but challenging. We evaluated the long-term outcome of patients with ISPN undergoing simultaneous cardiac and lung surgery.Methods The clinical records of 33 consecutive patients with ISPN undergoing cardiac and lung surgery, either simultaneously (n = 30) or sequentially (n = 3), were retrospectively evaluated and completed by detailed follow-up.Results On histological examination, 14 cases (42.4%) of primary NSCLC were identified. Benign findings consisted mostly of hamartoma and inflammation. Malignant ISPN were larger in size (22.5 ±  12.4 vs. 13.6 ±  8.6 mm) and ISPN with a diameter >10 mm had a higher incidence of malignancy compared to those ≤10 mm (56.0% vs. 0%). Patients undergoing concomittant heart and lung surgery received either a wedge resection (n = 26) or a lobectomy (n = 4). The 5-year survival of patients with malignant ISPN was lower than that of patients with benign ISPN (43.6% vs. 85.6%).Conclusions Our results corroborate a high incidence of malignancy in ISPN detected prior to scheduled cardiac surgery. Simultaneous cardiac and lung surgery for NSCLC appears to be associated with a poor long-term outcome.
Keywords: lung cancer treatment (surgery, medical); lung cancer; diagnosis (includes staging, imaging, fiducials); cardiac lung cancer; lung resection; cardiac surgery; solitary pulmonary nodule